The Influence Of Product Quality And Brand Image On Consumer Satisfaction Of Jago Coffee In Puri Kembangan, West Jakarta - Alkhaira, Yovy; Amirudin, Amirudin (Management Science Doctoral Program, Pasundan University, 2025)
This research aims to determine the influence of product quality and brand image on consumer satisfaction of Jago coffee in Puri Kembangan, West Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research are that product quality has a significant effect on consumer satisfaction of 38.8%. Hypothesis testing shows that t count > t table or (4.669 > 1.984). Brand image has a significant effect on consumer satisfaction of 52.8%, hypothesis testing obtained t count > t table or (7.531 > 1.984). Product quality and brand image simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 15.628 + 0.348X1 + 0.420X2 and an influence contribution of 61.5%, the hypothesis test obtained calculated F > F table or (76.718 > 2.70).